Zinovii Ostapovych Melnyk (1935-1983) - Bokalo, M.M.; Buhrii, O.M.; Kyrylych, V.M.; Slyusarchuk, O.Z. (Matematychni Studii, 2025)
The life and creative path of the outstanding scientist and Dean of the Faculty of Mechanics and Mathematics of Lviv University Z. O. Melnyk is considered